2011
DOI: 10.1182/blood-2011-06-362038
|View full text |Cite
|
Sign up to set email alerts
|

Proof of principle for transfusion of in vitro–generated red blood cells

Abstract: In vitro RBC production from stem cells could represent an alternative to classic transfusion products. Until now the clinical feasibility of this concept has not been demonstrated. We addressed the question of the capacity of cultured RBCs (cRBCs) to survive in humans. By using a culture protocol permitting erythroid differentiation from peripheral CD34 ؉ HSC, we generated a homogeneous population of cRBC functional in terms of their deformability, enzyme content, capacity of their hemoglobin to fix/release o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
364
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 300 publications
(395 citation statements)
references
References 44 publications
(42 reference statements)
9
364
0
11
Order By: Relevance
“…15 We recently established the proof of principle for transfusion of in vitro generated enucleated RBC in humans. 31 The approach we now report provides an alternative to functional normalization of sickle cell RBC for auto transfusion purposes in the hiPSC model. 5,11,15 In conclusion, using the model of hematopoiesis, we show for the first time that hiPSC can achieve terminal maturation, in vitro in terms of enucleation and in vivo in terms of synthesis of adult Hb.…”
Section: Discussionmentioning
confidence: 99%
“…15 We recently established the proof of principle for transfusion of in vitro generated enucleated RBC in humans. 31 The approach we now report provides an alternative to functional normalization of sickle cell RBC for auto transfusion purposes in the hiPSC model. 5,11,15 In conclusion, using the model of hematopoiesis, we show for the first time that hiPSC can achieve terminal maturation, in vitro in terms of enucleation and in vivo in terms of synthesis of adult Hb.…”
Section: Discussionmentioning
confidence: 99%
“…Giarratana et al have demonstrated that red cells can be generated efficiently starting from HSPCs derived from human peripheral blood. 7 The cells produced in this study were mature reticulocytes, they expressed adult hemoglobin, they bound oxygen in a reversible manner, and their rheological properties were similar to those of reticulocytes released in vivo into the circulation of healthy individuals. Giarratana and colleagues also showed for the first time that cultured RBCs persisted for several weeks after transfusion into a human volunteer.…”
mentioning
confidence: 98%
“…Conjugation of an imaging probe (i.e., a radioisotope), together with such a targeting moiety also could be used for diagnostic purposes. Further advances in the in vitro generation of human RBCs and genetic engineering of their precursors will provide a robust platform for the use of this surface-engineering method, possibly in conjunction with cytosolic modification, in clinical applications (11,(21)(22)(23)(24)(25)(26). Moreover, the established safety of blood transfusions inspires confidence that these engineered RBCs indeed will find use in humans.…”
Section: Sortagging and Cytosolic Modification Of Terminally Differenmentioning
confidence: 99%